European Works Councils in the pharmaceutical industry - Eleni Triantafillidou; Theodore Koutroukis (SPOUDAI - Journal of Economics and Business, 2022)
The purpose of this study is to provide an overview of institutional development of employee participation in Europe and analyze European Works Councils (EWC) agreements in the pharmaceutical industry. Mergers and acquisitions in the pharmaceutical industry increased the number of EWC agreements. There are now 30 multinational pharmaceutical companies with an active EWC. The first part of the study explores the legal aspects of European Works Councils and the European institutional and regulatory framework for employee participation. The second part of the study analyzes the characteristics and scope of EWC agreements using 5 case studies from the pharmaceutical sector. The source used to identify the EWC agreements is the European Trade Union Institute database and the research method used is legal analysis of constitutional framework and qualitative analysis of the agreements. The EWC agreements in the pharmaceutical sector provide the opportunity for management and employees for information and consultation on transnational issues concerning the company structure, the economic and financial situation of the company, the status and trend of employment and substantial changes concerning the company. Although EWC directives provide the framework for information and consultation on transnational level the constant changes in the structures of pharmaceutical companies and the increasing rates of mergers and acquisitions in the pharmaceutical sector make it difficult for EWC's to effectively participate in decision-making and influence managerial decisions.
Keywords: M54; J50; K30; 330; Employee participation; Employee Relations; European Works Councils; Human Resource Management